O048 Levosimendin use in high-risk cardiac patients - is it about timing?. (22nd July 2022) - Peacock, T; Anderson, B
Abstract: Introduction: Use of levosimendan pre-operatively has had mixed outcomes for cardiac patients with low ventricular ejection fraction (EF). Whilst studies have examined the effects of immediate preoperative and intraoperative administration, outcomes of administration one week prior to surgical intervention have not been evaluated. The aims of this study were to compare cardiac parameters pre and post administration of levosimendan one week prior to surgery. Method: A retrospective analysis was conducted of high-risk patients undergoing cardiac surgery. Patients with an EF of <50% were included. Baseline EF, pulmonary artery pressures (PAP), cardiac output (CO) and cardiac index (CI) were measured utilising transthoracic echocardiogram. A weight-based dose of levosimendan was administered one week prior to intervention. Measures were repeated pre-operatively, one week after administration of levosimendan (0.2mg/Kg). Results: A total of 100 patients were included in this study. The mean time from dose of levosimendan to operative time was 11 days. Mean EF, systolic PAP, mean PAP, CO, and CI were 43.63%, 48.71mmHg, 29.97mmHg, 4.84L/min, and 2.47L/min/m2 respectively. Each parameter showed significant improvement one week post levosimendan; 48.42% (p=0.011, SE 4.7, 1.8–1.2 95% CI), 35.06mmHg (p= <0.001, SE 13.65, 11.2–16.0 95% CI), 21.58mmHg (p= <0.001, SE 8.4, 6.6–10.1 95% CI), 5.64L/min (p= <0.001, SE 0.8, 0.6 to 1 95% CI), and 2.88L/min/m 2 (p<0.001, SE 0.4, 0.3–0.5 95% CI) respectively. Overall, 30-day mortality was 3% (n=3), compared to an expected mortality of 5.02%. Take-home message: Levosimendan shows promise in improving pre-operative cardiac function when given one week prior to intervention in high-risk cardiac patients.